Post facto, trends, pattern of Urbanity in Sikkim - Paul, Kalosona; Sharma, Deepak (Penerbit Universiti Kebangsaan Malaysia, 2016)
Urbanity is the rapid continues concentration of structuralism, modernism and socio-cultural dynamic changes through urbanization process. Urbanization has been viewed as an important factor in the areas of economic transformation, orchestrating the breakdown of the feudal order and taking societies to higher levels of social transformation. The paper analyses the spatial pattern, process and trend of urbanization in the state of Sikkim on the basis of conceptualization theory & secondary data for the last seven decades. Thus, till 1970, the process of urbanization was very invisible. Sikkim has also witnessed rapid urbanization process in the post-merger years and trend is rather increasing. A town attracts people for a better opportunity, employment, urban facility, better lifestyle and easy access to the places of human activities and also for better human status. The number of urban towns has grown from 1 in 1981 to 8 in 2001. The number of the population residing in urban areas has increased from 2% in 1951 to 11 in 2011. Even in Sikkim, the rural-urban migration is the pouring potency for growing the urban population. There is also an urgent need to strengthen the carrying capacity of smaller town to brace up to the challenges ahead by checking in the migration of population and through appropriate urban planning, monitoring & government intervention policies for effect in future on natural beauties as well as environmental resources.